Hardiness dengan Eudaimonic Workplace Well-Being pada Petugas Pemadam Kebakaran dan Penyelamatan - Ariani, Tiara Tri; Rahmi, Tuti (YASIN, 2025)
Workplace well-being has become an increasingly prominent topic in psychology, both nationally and internationally, particularly in the context of eudaimonic well-being, which emphasizes meaning and self-actualization in the workplace. One contributing factor to high eudaimonic workplace well-being is hardiness—the individual’s capacity to face stress with a sense of commitment, control, and challenge. This study aims to examine the relationship between hardiness and eudaimonic workplace well-being among firefighters and rescue officers in Bukittinggi City. A quantitative correlational method was employed, involving 43 field firefighters selected through total sampling. The instruments used included an Indonesian-adapted eudaimonic workplace well-being scale based on two dimensions: interpersonal and intrapersonal well-being, and a hardiness scale comprising the dimensions of commitment, control, and challenge. Spearman correlation analysis revealed a significant positive relationship between hardiness and eudaimonic workplace well-being (correlation coefficient = 0.417; p < 0.05). The study concludes that higher levels of hardiness are associated with greater eudaimonic well-being at work among firefighters. These findings offer practical implications for human resource management, particularly in fostering psychological resilience to enhance the quality of workplace well-being among fire and rescue personnel.